CXCL13 and CXCR5 are upregulated in PCOS mice ovaries but downregulated following metformin administration. (1st October 2022) - Ullah, Amin; Pervaz, Sadaf; Adu-Gyamfi, Enoch Appiah; Czika, Armin; Guo, Man; Wang, Mei-Jiao; Wang, Ying-Xiong
Abstract: Polycystic ovary syndrome (PCOS) is becoming a common pathology among women, yet its pathogenesis remains enigmatic. The chemokine C-X-C motif ligand 13 (CXCL13) and its receptor type 5 (CXCR5) regulate inflammatory responses but their roles in PCOS remain unknown. Metformin is commonly administered to PCOS patients but its mechanism of action remains unclear. Thus, we aimed to determine the expression of CXCL13 and CXCR5 in the ovaries of PCOS mice and to evaluate the therapeutic effect of metformin on them. The study comprised four groups of mice: control, PCOS, PCOS plus metformin, and PCOS plus vehicle. CXCL13 and CXCR5 were found to be elevated in the ovarian tissues of the PCOS mice. Metformin reduced ovarian CXCL13 and CXCR5 expressions in the PCOS mice. Hence, CXCL13 and CXCR5 are potentially involved in PCOS pathogenesis; and metformin may help alleviate the symptoms of PCOS by inhibiting CXCL13 expression and actions. Highlights: Serum CXCL13 concentrations were higher in PCOS mice than in normal controls but could be reversed by metformin. Metformin administration improved hormonal levels and the lipid profile of PCOS mice. Metformin administration partially resolved ovarian morphology in PCOS mice.